Laboratory, in situ and full-scale load tests to assess flood embankment stability on peat - Zwanenburg,C; Jardine,RJ (Geotechnique: international journal of soil mechanics, 2015)
The low submerged unit weights of peats usually lead to low effective self-weight stresses, stiffnesses and undrained shear strengths. These features, in combination with high compressibility, a propensity to creep and the uncertain effects of fibrous inclusions, make foundation stability hard to assess reliably. It is usual to apply high safety, or strong material reduction, factors in foundation design. However, over-conservatism can lead to undesirable environmental and financial costs. This paper describes full-scale field tests conducted on peat, with and without pre-loading, at Uitdam on the borders of Lake Markermeer, north of Amsterdam. The experiments investigated the peat layers' consolidation behaviour and their response under loading, including full shear failure. Noting the complex final test geometries and the large displacements developed, simple numerical analyses were undertaken to help interpret the failures within a Tresca and ‘consolidated undrained shear strength' framework. The trials that included modest pre-loading developed large vertical consolidation strains (up to 35%) and significant bearing capacity improvements. The field experiments provide a rich resource for testing advanced numerical techniques. They also allowed a range of practical characterisation techniques to be assessed and calibrated for flood dyke applications.